Virological surveillance of influenza and other respiratory viruses during six consecutive seasons from 2006 to 2012 in Catalonia, Spain. (June 2016) - Antón, A.; Marcos, M.A.; Torner, N.; Isanta, R.; Camps, M.; Martínez, A.; Domínguez, A.; Jané, M.; Jiménez de Anta, M.T.; Pumarola, T.
Abstract: Most attention is given to seasonal influenza and respiratory syncytial virus outbreaks, but the cumulative burden caused by other respiratory viruses (RV) is not widely considered. The aim of the present study is to describe the circulation of RV in the general population during six consecutive seasons from 2006 to 2012 in Catalonia, Spain. Cell culture, immunofluorescence and PCR-based assays were used for the RV laboratory-confirmation and influenza subtyping. Phylogenetic and molecular characterizations of viral haemagglutinin, partial neuraminidase and matrix 2 proteins were performed from a representative sampling of influenza viruses. A total of 6315 nasopharyngeal samples were collected, of which 64% were laboratory-confirmed, mainly as influenza A viruses and rhinoviruses. Results show the significant burden of viral aetiological agents in acute respiratory infection, particularly in the youngest cases. The study of influenza strains reveals their continuous evolution through either progressive mutations or by segment reassortments. Moreover, the predominant influenza B lineage was different from that included in the recommended vaccine in half of the studied seasons, supporting the formulation and use of a quadrivalent influenza vaccine. Regarding neuraminidase inhibitors resistance, with the exception of the 2007/08 H275Y seasonal A(H1N1) strains, no other circulating influenza strains carrying known resistance genetic markers were found. Moreover, all circulating A(H1N1)pdm09 and A(H3N2) strains finally became genetically resistant to adamantanes. A wide knowledge of the seasonality patterns of the RV in the general population is well-appreciated, but it is a challenge due to the unpredictable circulation of RV, highlighting the value of local and global RV surveillance.